Surface engineering of metals via metallographic etching for microstructural characterization - Jain, Ekta (Nanyang Technological University, 2021)
Metallography is the most utilised practice to analyse the microstructure of materials and interpret their properties. Most of the typically used characterisation methods are known to be complex and high-cost equipment setup and they often have limited field of view and low through-put. In this work, a simple and in-expensive novel optical-based method called directional reflectance microscopy (DRM) is used for inferring the grain orientation and compositional gradients in chemically etched metals and alloys. DRM relies on acquiring a series of optical micrographs of chemically etched metallic surfaces illuminated under different angles. Later, the angle-dependent reflectance of the sample surface enables us, to measure the orientation of the underlying crystal grains in metals and compositional heterogeneity in alloys.